2002
DOI: 10.1677/joe.0.1720489
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expression of chorionic gonadotrophin transcripts in prostate cancer by quantitative Taqman and a modified molecular beacon RT-PCR

Abstract: Expression of human chorionic gonadotrophin (hCG) is associated with trophoblastic, testicular and other malignancies such as bladder, pancreatic, cervical, breast and prostate cancer. In the prostate, however, hCG expression, associated with neuroendocrine cells, is also found in normal tissue. Of the six highly homologous genes that all encode the -subunit of hCG, the 7 gene is reportedly the only gene expressed in several non-transformed tissues. The 3, 5 and 8 genes would be variably expressed in malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
(26 reference statements)
1
21
3
Order By: Relevance
“…35 Based on these findings, malignant transformation has been thought to be associated with type II hCG␤ expression. However, earlier studies on RCC cell lines have shown a higher proportion (50 to 85%) of type I hCG␤ genes, 36 and in the present study, we detected type II gene expression in only two of the 42 positive tumors. Thus, expression of the various hCG␤ genes is both tissue and tumor specific, and aggressive tumor growth may be associated with increased expression of either gene type.…”
Section: Hcg␤ In Renal Cellcontrasting
confidence: 78%
See 1 more Smart Citation
“…35 Based on these findings, malignant transformation has been thought to be associated with type II hCG␤ expression. However, earlier studies on RCC cell lines have shown a higher proportion (50 to 85%) of type I hCG␤ genes, 36 and in the present study, we detected type II gene expression in only two of the 42 positive tumors. Thus, expression of the various hCG␤ genes is both tissue and tumor specific, and aggressive tumor growth may be associated with increased expression of either gene type.…”
Section: Hcg␤ In Renal Cellcontrasting
confidence: 78%
“…18,35,36 Type II genes are expressed in breast cancer tissue, 17 and increased expression of type II genes has been found to be associated with advanced stage in bladder cancer. 35 Based on these findings, malignant transformation has been thought to be associated with type II hCG␤ expression.…”
Section: Hcg␤ In Renal Cellmentioning
confidence: 99%
“…However, to obtain a smaller loop sequence, only one arm (shown in italics in the sequence above), complementary to five nucleotides at the 5Ј end of the hCG␤ sequence, was attached 3Ј (6,14 ). This produced a Molecular Beacon-type probe with excellent specificity for hCG␤-3, -5, and -8 mRNA without interference by transcripts from the hCG␤-7 or luteinizing hormone genes (6 ). PCR primers were designed with use of the Primer Express Software (PE Applied Biosystems).…”
Section: Molecular Beacon Designmentioning
confidence: 99%
“…Other malignancies, such as bladder (3,4 ), pancreatic, and cervical carcinomas (3 ) and prostate (5,6 ) and breast cancer (7)(8)(9)(10), also express hCG. This hormone is one of a family of related glycoproteins that includes luteinizing hormone, follicle-stimulating hormone, and thyroid-stimulating hormone.…”
mentioning
confidence: 99%
“…There were also a number of studies by other groups using Taqman based gene expression analysis with RNA extracted with TRIzol reagent [156][157][158][159][160][161][162] …”
Section: Taqman Gene Expression Assay Using Rna Extracted With Trizolmentioning
confidence: 99%